Correlates of Protection for Cholera. (20th October 2021) - Iyer, Anita S; Harris, Jason B
Abstract: A correlate of protection (CoP) is a measured adaptive immune response to vaccination or infection that is associated with protection against disease. However, the degree to which a CoP can serve as a surrogate end point for vaccine efficacy should depend on the robustness of this association. While cholera toxin is a dominant target of the human antibody response to Vibrio cholerae infection, antitoxin responses are not associated with long-term immunity, and are not effective CoPs for cholera. Instead, protection appears to be mediated by functional antibodies that target the O-polysaccharide coated V. cholerae outer membrane. Vibriocidal antibodies, which are complement-dependent bactericidal antibodies, remain the most accepted CoP for cholera and are used as surrogate end points in some vaccine studies. However, the association between vibriocidal antibody titers and immunity is not absolute, and they are unlikely to reflect a mechanistic correlate of protection against cholera.